The Colonial Machine - McClellan III, James E.; Regourd, François (Brepols, 2011)
The rise of modern science and European colonial and imperial expansion are indisputably two defining elements of modern world history. James E. McClellan III and François Regourd explore these two world-historical forces and their interactions in this comprehensive and in-depth history of the French case in the Old Regime presented here for the first time. The case is key because no other state matched Old-Regime France as a center for organized science and because contemporary France closely rivaled Britain as a colonial power, as well as leading all other nations in commodity production and participating in the slave trade. Based on extensive archival research and vast primary and secondary literatures and sharply reframing the historiography of the field, this landmark volume traces the development and significance for early-modern history of the Colonial Machine of Old-Regime France, an unparalleled agglomeration of institutions geared to the success of the French colonial enterprise, including the Royal Navy, the Académie Royale des Sciences, the Jardin du Roi, and a host of related specialist institutions working together at home and overseas. Mainly supported by the French state, the Colonial Machine reveals itself through its actions from the time of Colbert and Louis XIV as it grappled with fundamental problems facing contemporary European colonialism: cartography and navigation; medical care of sailors, colonists, and slaves; and applied botany and commodity production. Historians of globalization and European overseas expansion, of Old-Regime France, and of science in the seventeenth and eighteenth centuries will henceforth take this stimulating volume as a necessary starting point for further reflection and research.